Statistical Planetary Period Oscillation Signatures in Saturn's UV Auroral Intensity. Issue 10 (29th October 2018) - Bader, A.; Badman, S. V.; Kinrade, J.; Cowley, S. W. H.; Provan, G.; Pryor, W. R.
Abstract: Saturn's auroral emissions are a good measure of field‐aligned current (FAC) systems in the planet's magnetospheric environment. Previous studies based on magnetic field data have identified current systems rotating with the planetary period oscillations (PPOs) in both hemispheres, superimposed onto the local time‐invariant current system producing the main auroral emission. In this study we analyze the statistical behavior of Saturn's ultraviolet auroral emissions over the full Cassini mission using all suitable Cassini‐UVIS images acquired between 2007 and 2017. We examine auroral intensities by organizing the data by the two PPO coordinate systems. Strong statistical intensifications are observed close to the expected locations of upward FACs in both hemispheres, clearly supporting the main assumptions of the present theoretical model. We furthermore find clear signatures of modulation due to interhemispheric current closure from the PPO system in the opposite hemisphere, although with a weaker modulation amplitude. The auroral intensity in the northern hemisphere is shown to be modulated by a superposition of the FACs associated with both PPO systems, as the modulation phase and amplitude varies as expected for different relative orientations (beat phases) of the two PPO systems. Key Points: Saturn's UV auroral intensities are modulated in phase with rotating current systems through all local times and in both hemispheres The intensity modulation in each hemisphere is controlled by the superposition of currents originating in both hemispheres This marks the first unambiguous evidence of planetary period oscillation‐associated field‐aligned current flow effects in auroral data